Drought zone monitoring with remote sensing technology in Metro City, Indonesia - Utami, Rahma Kurnia Sri; Zulkarnain, Zulkarnain; Sudarmi; Halengkara, Listumbinang; Rahian, Farah Azzahra (Journal of Environment and Geography Education, 2024)
Background: Lampung Province, Indonesia, is prone to drought, with 232 villages experiencing drought in recent years according to data from the Central Statistics Agency (BPS). Metro City, a region within Lampung Province, is particularly susceptible to drought, as evidenced by a decrease in agricultural production due to drought conditions observed during a three-month period (December 2021–February 2022). Despite the agricultural sector being a crucial economic driver in the region, drought poses significant challenges. Remote Sensing and Geographic Information Systems (GIS) technologies offer efficient methods for identifying drought-prone areas with precision and accuracy. Methods: This research employs digital image processing techniques, specifically image transformation using various vegetation index algorithms such as the Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), and Normalized Difference Drought Index (NDDI). Landsat 8 OLI satellite imagery is utilized for data analysis, with Quantum GIS serving as the primary application for image processing. Findings: The research findings reveal the distribution of drought-prone zones on agricultural land in Metro City. Conclusion: The Central Metro District exhibits the lowest severity of drought classification, with an agricultural land area of 68.88 hectares classified as experiencing very severe drought. Conversely, the North Metro District is identified as having the most severe drought conditions, encompassing an area of 537.69 hectares.